Journal of the Egyptian Mathematical Society - Mekheimer, Khaled; Doha, Eid H.; Ali, Mohamed; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
Journal of the Egyptian Mathematical Society (JOEMS) is a journal of mathematical sciences publishing refereed, well-written original research articles that describe the latest research and developments in the areas of pure and applied mathematics. This is a broad-based journal covering mathematics and interdisciplinary research. To bring together original research thereby providing a forum for active researchers in mathematics and workers in more applied areas. To be acceptable for publication in the journal, papers must make significant, original and correct contributions to one or more of the fields mentioned in Mathematical Subjects Classification (M.S.C.). Applied Mathematics accepted papers should be clearly motivated by actual or potential application to real phenomena.
Keywords: Mathematics; Mathematics; Mathematical statistics; Mathematics; General Mathematics; Mathematical Statistics